View factors from a longitudinal strip to cylindrical segments and disk sectors. (February 2023) - Revanna, Thippeswamy G.; Katte, Subrahmanya S.
Highlights: View factor expression between the elements of cylinder are derived using contour integration method. Analytical expression for view factor between differential area, and segment & disk sectors on inner surface of cylinder has been derived. Analytical expression for view factor between longitudinal strip, and segment & disk sectors on inner surface of cylinder has been derived. Derived view factor expression between the finite elements of Cylinder are necessary in two dimensional thermodynamic analysis of tubular space radiator. Abstract: Analysis of temperature distribution and net radiation heat exchange in a cylindrical enclosure, when the temperature varies with the directions, requires view factors between relevant finite surfaces, viz. between a pair of finite cylindrical segments on the lateral surface, and between a finite cylindrical segment and a sector on the base disk. A review of literature shows that analytical expressions or data are not available for the referred view factors. In this paper, analytical expressions for the view factors from a differential area on the lateral surface of cylinder to cylindrical segments, and also to sectors on the base disk are derived by contour integration method. Such expressions are integrated analytically to obtain the view factors from a longitudinal strip element on inner lateral surface of cylinder to segments of cylinder, and sectors on base disk. A representative parametric study is carried out for the latter view factors. These expressions are applicable for the two dimensional analysis of space radiator tubes.